The Effect of Work Environment on Teacher Performance at the Nahdlatul Ulama Private Elementary School in Medan - Fatimah Pohan; Nurul Ajima Ritonga (Majapahit Journal of Islamic Finance and Management, 2026)
The significance of the work environment in bolstering teacher performance in private primary schools served as the impetus for this study. At Nahdlatul Ulama Private Elementary School in Medan, the goals were to assess the state of the workplace, the caliber of teacher performance, and the impact of the workplace on teacher performance. The study used basic regression analysis as part of a quantitative methodology. Nine teachers made up the population; all of them participated in the study as responders. A questionnaire on a five-point Likert scale was used to gather data. Prior to hypothesis testing, normality and linearity tests were required. The results show that teacher performance is classified as very good with a mean score of 3.40, and the work environment is classified as very good with a mean score of 3.37. With a correlation value of 0.069 and a coefficient of determination of 0.005, regression results, however, do not demonstrate a positive and substantial impact of the work environment on teacher performance. This indicates that whereas other factors impact 99.5% of teacher effectiveness, the work environment only affects 0.5% of it. These results imply that in order to enhance teacher performance and contribute to the creation of school management policies, more factors should be taken into account.